On the issue of vegetation forage land northwestern part of the Talas region of Jambul Region (Eurasian Journal of Ecology, 2016)
This article presents the results of a study of vegetation fodder lands north-western part of the Talas region of Jambul Region. Made taxonomic analysis of vegetation of the study area (119 species from 88 genera and 27 families). Identified the dominant family. Given botanical descriptions of the main forage plants. Discusses nutrition and palatability of these power plants.
Keywords: pastures; hayfields; study area; life forms